Desenvolvimento de peptideo bioativo modulador da resposta immune - Vaz, Emília Rezende (2014)
Autoimmune diseases are a group of different diseases which are characterized by an immune disorder leading to decreased tolerance to components of the body itself. These diseases have many factors that trigger such as a decrease of the share or percentage of regulatory T cells (Tregs). The Transforming Growth Factor-beta 1 (TGF-β1) is involved in the suppression of the inflammatory response during the pathogenesis of autoimmune diseases (juvenile idiopathic arthritis, multiple sclerosis, diabetes), through the activation of this cell type. This cytokine is also associated with modulation of an inflammatory response either by increasing Treg cells and by modulating proinflammatory cytokines such as tumor necrosis factor alpha (TNF-α). The components found in both innate immune responses as adaptive must be considered potential targets for developing new drugs immune modulators. Thus, manipulation of Tregs is an attractive strategy for immunotherapy and hence, the use of mimetic peptide to TGF-β1 can be adopted to reduce the effects of severe autologous response, then creating an additional therapy for autoimmunity as well as for the treatment of inflammatory diseases. Our results show that we can select TGF-β1 mimetic peptides since we can prove by bioinformatics both bind to this receptor molecule. Thus, the peptides can be used as immunomodulators to combat inflammation and in the treatment of autoimmune diseases since they can modulate the production of TNF-α and IL-10.